2006
DOI: 10.1007/s11010-006-1522-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of increased iron status in moderately exercised rats

Abstract: Although iron plays a critical role in exercise, the regulatory mechanism of iron metabolism remains poorly understood. The aims of the present study were to investigate the effects of different intensity exercise on body iron status and the regulatory mechanism of duodenal iron absorption. Thirty female Sprague-Dawley rats (90-100 g) were randomly divided into three groups: a control group (remained sedentary, CG), a moderately exercised group (swam 1.5 h/day, MG) and a strenuously exercised group (swam with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
5
21
0
Order By: Relevance
“…In the present investigation, the Dmt1 band, which was much stronger in the b/b rats, was noted at slightly Ͼ55 kDa; other bands on blots were of similar intensity in ϩ/bs and b/bs, likely representing nonspecific signals. A survey of the primary literature reveals a wide discrepancy in the molecular weight of Dmt1 in Western blot analyses, with variations in rodent and human intestine noted from ϳ43 to 85 kDa (34,36,37,57,59). The molecular weight of the Dmt1 detected in the present studies thus falls within ranges reported elsewhere, and its strong induction in the b/b rats lends confidence to it being specific.…”
Section: Discussionsupporting
confidence: 71%
“…In the present investigation, the Dmt1 band, which was much stronger in the b/b rats, was noted at slightly Ͼ55 kDa; other bands on blots were of similar intensity in ϩ/bs and b/bs, likely representing nonspecific signals. A survey of the primary literature reveals a wide discrepancy in the molecular weight of Dmt1 in Western blot analyses, with variations in rodent and human intestine noted from ϳ43 to 85 kDa (34,36,37,57,59). The molecular weight of the Dmt1 detected in the present studies thus falls within ranges reported elsewhere, and its strong induction in the b/b rats lends confidence to it being specific.…”
Section: Discussionsupporting
confidence: 71%
“…It was argued that exercise modifi ed distribution of iron in various tissues (25) and also that moderate exercise had a regulatory effect on body iron values (26). The results we found in relation to the iron parameter in our study are congruous with the results of the above-cited researchers.…”
Section: Tab 3 Levels Of Copper Iron Calcium Zinc and Selenium Isupporting
confidence: 85%
“…In brief, we agree with Sawka et al [5] and Warburton et al [32] that the above-mentioned discrepancies are likely related to differences in participant sampling, experimental conditions and/or the season in which the research was conducted. For example, 10 weeks of moderate swimming in rats increased iron status, Hb and HCT, while strenuous swimming caused the variables to change in the opposite direction [34]. Initial Hb and HCT levels likely influence training effects on erythropoiesis.…”
Section: Effects Of Exercise Training On the Erythrocytic Systemmentioning
confidence: 99%